Re-evaluation of the efficacy and safety of anti-Aβ monoclonal antibodies (lecanemab/donanemab) in the treatment of early Alzheimer’s disease - Wang, Haoyang; Pan, Junying; Zhang, Mingming; Tan, Zengde (Frontiers in Pharmacology, 2025)
ObjectiveTo systematically evaluate the efficacy and safety of anti-Aβ monoclonal antibodies (Lecanemab/Donanemab) in the treatment of early Alzheimer’s disease (AD) and to provide evidence for rational clinical use.MethodsWe searched databases including PubMed, Embase, Cochrane, Web of Science, CNKI, and the Chinese Biomedical Literature Database for relevant literature on the use of anti-Aβ monoclonal antibodies in treating early AD. Two reviewers independently screened the literature, extracted data, and conducted meta-analysis using RevMan 5.4.ResultsA total of five clinical studies were included. Meta-analysis results showed that in terms of clinical outcomes, Lecanemab/Donanemab outperformed the control group in ADCOMS, CDR-SB, ADAS-Cog 14, and amyloid burden on PET. Regarding safety, the relative risk of amyloid-related imaging abnormalities (ARIA) in patients treated with Lecanemab/Donanemab was 4.35 times higher than the control group, with significantly higher risks of ARIA-E and ARIA-H. Among other adverse events, the risk of superficial siderosis of the central nervous system was notably higher and statistically significant.ConclusionLecanemab/Donanemab can improve memory, cognitive function, and daily living abilities in patients with early AD, significantly reduce the composite score of Alzheimer’s disease, and inhibit the accumulation of amyloid peptides, thereby alleviating symptoms and improving the condition.